TINJAUAN YURIDIS TERHADAP ANAK YANG MENJADI KURIR NARKOTIKA DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Edy Supriyanto (Lembaga Penelitian Universitas Trisakti, 2018)
Narcotics dealers take advantage of minors to be courier drugs with the aim to fool the authorities. Lack of knowledge of narcotics, and the inability to resist and resist the underage child are targeted by narcotics to circulate narcotics widely and veiled. The research method used is normative legal research. The approach used is a qualitative approach that is the research method that produces descriptive data. There is a legal protection effort under the Criminal Justice System Act through a restorative justice approach to the achievement of diversion and is based on the discretion of law enforcement to keep children from imposing the punishment and stigmatization of the child for its growth to grow into an adult. Constraints in the context of legal protection of children as drug couriers one of them is that the narcotics laws do not limit the age in the judiciary be it adults and minors, so the child as a narcotics courier can still be punished when the ability of children who are still limited and not perfect people adult who should be noticed by law enforcement officers in applying criminal punishment for child offenders of narcotics crime.